Implementation Attacks on ML-KEM: Analysis, Practical Assessment, and Recommendations - Moia, Vitor Hugo Galhardo; Novaes, Kevin Pires; Rossetto, Vinicius de Paula (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2026)
ML-KEM is the NIST-standardized key encapsulation mechanism derived from CRYSTALS-Kyber, a post-quantum cryptographic algorithm designed to provide security against both classical and quantum computers. However, implementation attacks threaten the adoption of this algorithm, specially in constrained environments (e.g., IoT, OT/ICS, and other embedded applications). In this work, we present an analysis of Side-Channel and Fault Injection attacks, demonstrating which algorithm operations are targeted by adversaries, practical experiments to detect side-channel leakage, adversary capabilities required to perform attacks, and recommendations for securing implementations.